Comparison of various silica‐based monoliths for the analysis of large biomolecules†. Issue 14 (15th July 2013) - Vuignier, Karine; Fekete, Szabolcs; Carrupt, Pierre‐Alain; Veuthey, Jean‐Luc; Guillarme, Davy
<x xml:space="preserve">Abstract</x> In the present study, three types of silica‐based monoliths, i.e. the first and second generations of commercial silica monolithic columns and a wide‐pore prototype monolith were compared for the analysis of large biomolecules. These molecules possess molecular weights between 1 and 66 kDa. The gradient kinetic performance of the first‐generation monolith was lower than that of the second generation, for large biomolecules (>14 kDa) but very close with smaller ones (1.3–5.8 kDa). In contrast, the wide‐pore prototype column was particularly attractive with proteins larger than 19 kDa (higher peak capacity). Among these three columns, the selectivity and retention remained quite similar but a possible larger number of accessible and charged residual silanols was noticed on the wide‐pore prototype material, which led to unpredicted small changes in selectivity and slightly broader peaks than expected. The peak shapes attained with the addition of 0.1% formic acid in the mobile phase remained acceptable for MS coupling, particularly for biomolecules of less than 6 kDa. It was found that one of the major issues with all of these silica‐based monoliths is the possible poor recovery of large biomolecules (principally with monoclonal antibody fragments of more than 25 kDa).